2012
DOI: 10.1186/1478-4491-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Information systems on human resources for health: a global review

Abstract: BackgroundAlthough attainment of the health-related Millennium Development Goals relies on countries having adequate numbers of human resources for health (HRH) and their appropriate distribution, global understanding of the systems used to generate information for monitoring HRH stock and flows, known as human resources information systems (HRIS), is minimal. While HRIS are increasingly recognized as integral to health system performance assessment, baseline information regarding their scope and capability ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 9 publications
1
52
0
Order By: Relevance
“…The educational composition of the nursing workforce can vary widely in some countries. All of these have implications for nursing workforce composition—the mix of educational levels within the profession and how those translate into frontline direct care provision roles (Riley et al., ). The factors previously described are those directly associated with frontline service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The educational composition of the nursing workforce can vary widely in some countries. All of these have implications for nursing workforce composition—the mix of educational levels within the profession and how those translate into frontline direct care provision roles (Riley et al., ). The factors previously described are those directly associated with frontline service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…However, most available data sources have shortcomings [8,9]. A recent inventory of the requirements for a Human Resources Information System (HRIS) identified pay roll data as one of the nine components needed for data collection, but showed that these data are hard to collect [10]. Only in 10% of the 63 countries under review were these data available, with the result that the availability of pay roll data was ranked as the second-lowest component.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why a previous systematic review on HRIS in health 64 did not identify any research prior to 2000, whereas our review, using a broader range of search terms, found 7 such studies. Therefore, we recommend that researchers go beyond obvious keywords (eg, HRIS) when undertaking background research for new projects (for list of relevant keywords, see 9 ).…”
Section: Discussionmentioning
confidence: 71%